Activity of synthetic peptides against Chlamydia. Issue 6 (20th November 2017) - Donati, Manuela; Cenacchi, Giovanna; Biondi, Roberta; Papa, Valentina; Borel, Nicole; Vecchio Nepita, Edoardo; Magnino, Simone; Pasquinelli, Gianandrea; Levi, Aurora; Franco, Octavio L.
Abstract: The in vitro activity of six synthetic peptides against 36 strains of Chlamydia from different origins was investigated. Clavanin MO (CMO) proved to be the most active peptide, reducing the inclusion number of all Chlamydia strains from eight different species tested by ≥50% at 10 µg mL −1 . Mastoparan L showed an equal activity against C. trachomatis, C. pneumoniae, C. suis, and C. muridarum, but did not exert any inhibitory effect against C. psittaci, C. pecorum, C. abortus, and C. avium even at 80 µg mL −1 . These data suggest that CMO could be a promising compound in the prevention and treatment of chlamydial infections. Abstract :